TDOA Wireless Localization Comparison Influence of Network Topology - Oussalah, Mourad; Li, Hao (Discoveries in Agriculture and Food Sciences, 2014)
The interest to wireless positioning techniques has been increasing in recent decades due to wide spread of location-based services as well as constraints imposed by regulator on cellular operator to achieve an accepted level of cellular accuracy regardless of availability of GPS signals. Nevertheless, failure of some base stations cannot be fully avoided, yielding various cellular topologies, which, in turn would likely influence the accuracy of the positioning. This paper explores four types of cellular topologies: balanced, circular, U-shape and linear, which can be inferred from balanced topology structure. Assuming time difference of arrival technology and, up to some extent, time of arrival technology were employed, least square like methods are contrasted with maximum likelihood, Taylor, Chan and hybrid approaches in a simulation platform